Screening of external magnetic perturbation fields due to sheared plasma flow. (29th July 2016) - Li, L.; Liu, Y.Q.; Liang, Y.; Wang, N.; Luan, Q.; Zhong, F.C.; Liu, Y.
Abstract: Within the single fluid resistive magnetohydrodynamic model, systematic toroidal modelling efforts are devoted to investigate the plasma response induced screening of the applied external 3D magnetic field perturbations in the presence of sheared toroidal flow. One particular issue of interest is addressed, when the local flow speed approaches zero at the perturbation rational surface inside the plasma. Subtle screening physics, associated with the favourable averaged toroidal curvature effect (the GGJ effect (Glasser et al 1975 Phys. Fluids 7 875)), is found to play an essential role during slow flow near the rational surface by enhancing the screening at reduced flow. A strong cancellation effect between different terms of Ohm's law is discovered, leading to different screening physics in the GGJ regime, as compared to that of conventional screening of the typical resistive-inertial regime occurring at faster flow. These modelling results may be applicable to interpret certain mode locking experiments, as well as type-I edge localized mode suppression experiments, with resonant magnetic field perturbations being applied to tokamak plasmas at low input toroidal torque.